Simulation of mechanical behavior and multi-scale performance analysis of complex microstructural models in composite material layer design - Hailiang Su; Qiulin Qin; Deng An; Tengteng Wei; Zhe Han; Yuyan He; Guogui Huang (Polymer Testing)
To examine the impact of the intricate microstructural features of glass fiber reinforced polymer on the macroscopic performance of composite materials, a multi-scale analysis was carried out on the composite leaf spring, utilizing the detailed characteristics of the complex microstructures. Initially, a representative volume element incorporating an interface structure was developed, and its mechanical properties along with microscopic damage behaviors were predicted. Subsequently, the validity of the predicted mechanical behavior was corroborated through multi-directional tensile tests and scanning electron microscopy. Building upon this, a multi-scale analysis approach integrating interface damage modes with layer stacking ratios was proposed, providing a thorough investigation into the relationship between the microstructure and stacking angles of composite leaf springs. The design of composite layers was implemented to optimize the mechanical performance of the leaf springs. The analysis reveals that changes in the material microstructure lead to a shift in the primary load-bearing component of the polymer-based composite materials, thereby affecting the structural performance of the leaf spring. Ultimately, the fatigue life of the composite leaf spring was predicted, and the accuracy of these prediction results was validated.